Application of neural network technologies for the development of cluster structure of the territorial and administrative entities - M. G. Rodionov; A. M. Samarin (Вестник СибАДИ, 2017)
The article dwells upon the main factors influencing on investment attractiveness of the territorial and administrative entities. The authors present a simple neural network for evaluation of factors influencing on investment attractiveness. There are determined the main problems affecting the assessment of investment potential and the prospects of socio-economic development of the Omsk region. There is considered the project of the cluster approach to economic development. The methods of assessing efficiency of integrated economic structures’ activity are presented. There are considered the different types of assessments of cluster formations. There is determined the efficiency of creating and functioning cluster structures as an independent territorial and production entity.